Validity of Derivative Calculus Textbook to Increase Learning Motivation - Muhammad Taqwa (Program Studi Pendidikan Matematika Universitas PGRI Kanjuruhan Malang, 2023)
The purpose of this research is to develop a valid textbook in fostering student learning motivation. This type of research is development research, namely the development of textbooks with the Plomp model: (1) initial investigation, (2) design, (3) realization/construction, (4) testing, evaluation and revision, (5) implementation. The subjects of this study were students of the Mathematics Education Study Program of STKIP Andi Matappa. Research instrument: textbook validation sheet. Research results: the content validity score of the coursebook is included in the high category. This shows that the derivative calculus textbook that has been developed meets the validity elements to foster student learning motivation.